Peran Pemerintah dalam Ketahanan Pangan Nasional: Tinjauan Literatur Sistematis dan Analisis Bibliometrik - Nurhayati; Winda Roselina Effendi; Ramon Zamora; Utami Yerikania (Research and Development Agency Ministry of Home Affairs, 2026)
This study examines the role of government in strengthening national food security through a hybrid approach combining a systematic literature review (SLR) and bibliometric analysis. Literature data were collected from the Scopus database using the query